Cyber Literature as a Media for Reading Popular Literature Among Gen-Z - Faiza, Dinar; Bestari, Ade Christanty Yudha; Mayekti, Meilina Haris (International Journal of English and Applied Linguistics (IJEAL), 2024)
This research aims to determine the development of literature in the digital era which has shifted to cyber literature and also determine the existence of popularity of cyber literature among Gen-Z, the young generation whose demographic is already quite large 27.94% of the total population in Indonesia. It used a descriptive qualitative research methods with data collection through questionnaires and documentation. The questionnaire was used to determine the existence of cyber literature as a popular literature media among Gen-Z. This questionnaire was given to 100 respondents who were born in 1994-2010 (aged around 14-29 years old) so they were included in the Gen-Z group. The research results show that around 96% of respondents have read cyber literature and 55% have cyber literature accounts. Around 42.6% of Gen-Z said that the average intensity of using cyber literature was once a week and 29.7% said that they used literary applications around 1-3 times a week. The majority of Gen-Z think that cyber literature is easy and practical to use, can be accessed for free, provides a wide variety of interesting and up-to-date stories from local and international sources and can increase their literacy and knowledge, especially in terms of language and literature.